STUDENT WORKSHEET DESIGN (LKPD) BASED ON THINK PAIR SHARE (TPS) COOPERATIVE LEARNING MODEL JUNIOR HIGH SCHOOL STUDENTS - Putri Maisyarah (RADJA PUBLIKA, 2022)
The purpose of this study was to determine the design of LKPD based on the TPS learning model for junior high school students. This research model is the ADDIE development model which consists of five stages, namely Analysis, Design, Development, Implementation, Evaluation, but in this study the researchers limited it only to the development stage. (Development). The subjects of this study were six experts consisting of two mathematics education lecturers and one mathematics teacher as a material expert as well as two mathematics education lecturers and one mathematics teacher as a media expert. While the object is LKPD based on TPS learning model. The research instrument used was a learning media questionnaire. Consists of a questionnaire of material experts and media experts. Based on data analysis, the average value obtained by material experts is 4.3 and media experts is 4.4. From these results, it can be stated that the mathematics learning media meets the validity requirements of the learning media with an overall average value of 4.3 including in the Very Good category. Thus, from the validation results it can be stated that the LKPD based on the TPS learning model meets the validity requirements and is declared eligible.